Market Concentration, Asset Growth, And Islamic Bank Performance In Indonesia: A Panel Data Approach With NPF As Moderator - Hamida, Hamida; Indah Lestari, Wini (Program Studi Perbankan Syariah, IAIN Palopo, 2025)
This study aims to determine and analyze the effect of market concentration and asset growth on the financial performance of 9 Islamic banks in Indonesia from 2019 to 2023; market concentration using market share indicators, and financial performance using the Return On Assets (ROA) ratio. The research approach used is a quantitative approach. The type of data used in this study is panel data because this study involves data from 9 Islamic banks over a 5-year period (2019-2023). The data is secondary data taken from the company's financial statements or annual reports, related literature and documentation. The results showed the significance value of market concentration (X1) on ROA (Y) of 0.0719 which is greater than 0.05 or 0.0719> 0.05 and the calculated t value is smaller than the t table, namely 1.8477 < 2.01954, so hypothesis 1 is rejected, meaning that market concentration has no significant effect on Return On Asset. The significance value of asset growth (X2) on ROA (Y) of 0.000 is smaller than 0.05 or 0.000 <0.05 and the t value is greater than the t table, namely 5.5979> 2.01954, so hypothesis 2 is accepted, meaning that asset growth has a significant effect on Return On Asset. The results of NPF (Z) moderation testing, in the first analysis, namely the effect of NPF (Z) on ROA (Y), the results are significant because 0.005 <0.05. The second analysis is the interaction of X1*Z and X2*Z, the results obtained where the significance value of the X1*Z interaction is 0.483> 0.05 (not significant) and the X2*Z interaction value is 0.502> 0.05 (not significant). So it is concluded that NPF (Z) is not able to moderate the effect of market concentration (X1) and asset growth (X2) on ROA (Y).